Pengalaman Mahasiswa Terhadap Stres Akademik: Pendekatan Fenomenologis - Rafifah Nabila; Sri Nurhayati Selian (Jurnal Konseling dan Psikologi Indonesia, 2026)
In the academic environment, student are often faced with various academic demands that can lead to psychological pressure. Understanding students’ experiences in interpreting peer social support as a form of protection against academic stress is the main focus of this study. Academic stress is viewed as psychological pressure that arise from high academic demands, excessive, workload, and expectations from lecturers and oneself to achieve optimal performance. Peer social support plays an important role in helping students adapt and manage the pressures they experience. This study employed a qualitative approach with a phenomenological design to explore students’ subjective experiences in receiving and assigning meaning to peer social support. The participants consisted of 3 active students from different study programs, selected through purposive sampling based on criteria of having experienced academic stress and maintaining active social relationships with peers. Data were collected through semi structured in depth interviews and analyzed using thematic analysis to identify patterns and meanings within participants’ experiences. The findings reveal that peer support is perceived as emotional and social protection that helps students cope with academic pressures through empathy, tangible assistance, advice, and motivation. Such support serves as a source of psychological resilience that not only reduces stress levels but also strengthens students’ sense of belonging, acceptance, and well-being within the university environment.